2017
DOI: 10.1016/j.marpolbul.2017.01.039
|View full text |Cite
|
Sign up to set email alerts
|

Can environmental pollution by metals change genetic diversity? Ucides cordatus (Linnaeus, 1763) as a study case in Southeastern Brazilian mangroves

Abstract: Industrial areas on estuarine systems are commonly affected by heavy metals, affecting all local biota. Random Amplified Polymorphic DNA (RAPD) was used to evaluate genetic diversity of Ucides cordatus at mangroves in southeastern Brazil (Juréia, J; São Vicente, SV; and Cubatão, C), with distinct pollution levels by metals. The genetic diversity of this species was compared with concentrations of metals (Cd, Pb, Cu, Cr and Hg) in the environment. A pollution gradient was confirmed (SV>C>J), with low levels det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 64 publications
0
3
0
5
Order By: Relevance
“…VCS very coarse sand, CS coarse sand, MS median sand, FS fine sand, VFS very fine sand, SC silt-clay Venturini et al 2012). Although no pollutant was evaluated in the present work, previous studies in the region have shown the presence of contaminants (heavy metal and plastic residues) in the sediments of urbanized mangroves (Cordeiro and Costa 2010;Pinheiro et al 2013;Banci et al 2017). Therefore, we can assume that these pollutants may be affecting the mollusk assemblages, especially the infauna.…”
Section: Discussionmentioning
confidence: 82%
“…VCS very coarse sand, CS coarse sand, MS median sand, FS fine sand, VFS very fine sand, SC silt-clay Venturini et al 2012). Although no pollutant was evaluated in the present work, previous studies in the region have shown the presence of contaminants (heavy metal and plastic residues) in the sediments of urbanized mangroves (Cordeiro and Costa 2010;Pinheiro et al 2013;Banci et al 2017). Therefore, we can assume that these pollutants may be affecting the mollusk assemblages, especially the infauna.…”
Section: Discussionmentioning
confidence: 82%
“…Furthermore, short duration of larval stages often leads to strong subdivision of bivalve populations (Ye et al ., 2015). However, temporal, environmental or oceanographic factors instead of geographic factors may hamper gene flow with a subsequent effect on population sub-structure (Banci et al ., 2017; Gutierrez et al ., 2017). Genetic variability of distant populations may be affected by historical evolutionary events such as bottleneck effects, reduction in the effective population size and formation of barriers to gene flow (Geraghty et al ., 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Larvae of marine molluscan species come up against a passive dispersal through sea currents, resulting in the absence of genetic differentiation among distant geographic populations (Larsson et al ., 2016). Instead, oceanographic, temporal or environmental factors rather than geographic ones may form barriers to gene flow with an eventual effect on population sub-structure (Wu et al ., 2016; Banci et al ., 2017; Gutierrez et al ., 2017). Particularly in the Aegean Sea, following the intense water mass circulation (Olson et al ., 2007) that may favour gene flow among molluscan bivalve populations, absence of or small genetic differentiation has been revealed in the Mediterranean mussel populations through different genetic markers (Giantsis et al ., 2014 a , 2014 b ).…”
Section: Introductionmentioning
confidence: 99%